1995
DOI: 10.1177/0148607195019004296
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone, Glutamine, and a Modified Diet Enhance Nutrient Absorption in Patients With Severe Short Bowel Syndrome

Abstract: The combined administration of growth hormone, glutamine, and a modified diet enhanced nutrient absorption from the remnant bowel after massive intestinal resection. These changes occurred in a group of patients that had previously failed to adapt to the provision of enteral nutrients. This therapy may offer an alternative to long-term dependence on total parenteral nutrition for patients with severe short bowel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
103
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 246 publications
(105 citation statements)
references
References 35 publications
0
103
1
1
Order By: Relevance
“…In another open-labeled study, 32 the combination of growth hormone, glutamine, and high-carbohydrate diet improved energy absorption approximately 590 KJ/day in 8 short-bowel patients who all had preserved colonic continuity, which possibly was a result of the increase in carbohydrate intake known to increase energy absorption in patients with a colon. 39 In comparison, we found that GLP-2 increased absorption 440 kJ/day on a fixed diet.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In another open-labeled study, 32 the combination of growth hormone, glutamine, and high-carbohydrate diet improved energy absorption approximately 590 KJ/day in 8 short-bowel patients who all had preserved colonic continuity, which possibly was a result of the increase in carbohydrate intake known to increase energy absorption in patients with a colon. 39 In comparison, we found that GLP-2 increased absorption 440 kJ/day on a fixed diet.…”
Section: Discussionmentioning
confidence: 97%
“…27 Therefore, the search for factors to enhance small bowel adaptation and to increase the assimilation of macronutrients and absorption of water and electrolytes, thereby decreasing the need for parenteral nutrition, has been intensive. The concept of "bowel rehabilitation" was introduced by Byrne et al 31,32 with the introduction of growth hormone and glutamine in the treatment of short-bowel patients. However, their encouraging results have been disputed in later randomized, double-blinded studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 At 2 years, 57% of patients were independent of PN. 70 This is contrary to the results of Scolapio et al , who repeated a randomized, 6-week, double-blind, placebo-controlled, crossover study with similar treatment conditions to those of Bryne et al 68,69 and Weiming et al 70 but who reported only modest improvements in electrolyte absorption and no improvement in small bowel morphology, stool losses, or macronutrient absorption. 5,56 In pediatric case studies long-term low-dose rhGH treatment combined with glutamine supplementation and HCLF diet has 71 Two further case studies have shown increased tolerance to enteral feeding, and decreased stool output following rhGH treatment.…”
Section: Clinical Experiencementioning
confidence: 76%
“…68,69 At 1 year following the study 40% of patients treated with rhGH remained PN-independent. 69 Similarly, 3 weeks of treatment with rhGH, glutamine, and HCLF diet was associated with significant improvements in intestinal absorptive capacity and plasma levels of proteins in adult PN-dependent SBS patients.…”
Section: Clinical Experiencementioning
confidence: 99%